2018
DOI: 10.1016/j.sdentj.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of two mouth rinse sprays in inhibiting Streptococcus mutans growth on toothbrush bristles

Abstract: Although both mouth rinses were effective against toothbrush contamination, chlorhexidine gluconate proved to be better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…31 CHX is non-toxic, non-irritant, highly effective, rapid in action, and easy to use. 32 Also, it has a prominent role in reduction of bacterial plaque. [33][34][35] The mechanism of action of CHX is based on the attachment of positively charged CHX digluconate molecules with the negatively charged bacterial cell wall.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 CHX is non-toxic, non-irritant, highly effective, rapid in action, and easy to use. 32 Also, it has a prominent role in reduction of bacterial plaque. [33][34][35] The mechanism of action of CHX is based on the attachment of positively charged CHX digluconate molecules with the negatively charged bacterial cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some researchers reported that CHX reduced the microbial count of the toothbrush within a short span and the effects were much longer lasting compared with the other mouthrinses. 26,32 Talaat et al sprayed the toothbrush 6 times with 0.12% CHX from a 5 cm distance and found that its bacterial colony counts were significantly lower compared to rinsing with distilled water. 32 Our results were different from their study when we rinsed the toothbrush only 1 time with CHX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plaque begins to form with the accumulation of Gram-positive streptococci, followed by increasing deposits, which involve Gram-negative anaerobic bacteria. A recent study on a mouth rinse spray containing 0.03% TCS, Plax ® , showed that the growth of S. mutans is inhibited by this mouth rinse on toothbrush bristles that were used by children [ 82 ].…”
Section: Pharmacological Activities Of Tcsmentioning
confidence: 99%
“…Gel preparations have to be applied with gentle care but cannot be reached to all sites of mouth. 6 To overcome these difficulties an approach was made to prepare a convenient mouth dissolving poly herbal film, and these films get dissolved within a quick period in the mouth without chewing or drinking water or. A novel oral fast-dissolving films offers simple administration method with the convenience of dosing without water.…”
mentioning
confidence: 99%